The contribution of nutrient metal acquisition and metabolism to Acinetobacter baumannii survival within the host - Mortensen, Brittany L.; Skaar, Eric P. (Frontiers in Cellular and Infection Microbiology, 2013)
Acinetobacter baumannii is a significant contributor to intensive care unit (ICU) mortality causing numerous types of infection in this susceptible ICU population, most notably ventilator-associated pneumonia. The substantial disease burden attributed to A. baumannii and the rapid acquisition of antibiotic resistance make this bacterium a serious health care threat. A. baumannii is equipped to tolerate the hostile host environment through modification of its metabolism and nutritional needs. Among these adaptations is the evolution of mechanisms to acquire nutrient metals that are sequestered by the host as a defense against infection. Although all bacteria require nutrient metals, there is diversity in the particular metal needs among species and within varying tissue types and bacterial lifecycles. A. baumannii is well-equipped with the metal homeostatic systems required for the colonization of a diverse array of tissues. Specifically, iron and zinc homeostasis is important for A. baumannii interactions with biotic surfaces and for growth within vertebrates. This review discusses what is currently known regarding the interaction of A. baumannii with vertebrate cells with a particular emphasis on the contributions of metal homeostasis systems. Overall, published research supports the utility of exploiting these systems as targets for the development of much-needed antimicrobials against this emerging infectious threat.